Black and green : Afro-Colombians, development, and nature in the Pacific lowlands - Asher, Kiran (e-Duke books scholarly collection., 2009)
Looks at development of Afro-Colombian communities after passage of a 1991 law granting cultural rights and collective land ownership to the communities, arguing that social movements are often partially co-opted by market or state, but then use state res